Normative data for Frequency Patterns Test in assessment of Central Auditory Processing Disorders for South African children aged 8 to 11 years. - Mbele, Nomhle (Department of Health and Rehabilitation Sciences, 2023)
Background: A central auditory processing disorder (CAPD) is a disorder that presents in individuals as having difficulty understanding fast and degraded speech, understanding verbal instructions, and struggling to hear in background noise, these difficulties are not due to a peripheral hearing loss. Additional secondary effects of CAPD have been well documented to affect school aged children, therefore, making early diagnosis and intervention important for their development. The central tests currently used for testing in South Africa have materials and normative data that were developed from an American population of English first language speakers. In addition, many of the tests in the assessment battery have a high linguistic load. This raises a challenge in the South African population of first language English speakers and the majority of the population who are not first language English speakers. To reduce misdiagnosis, it is important to generate context-specific normative data from a South African test population. By developing normative data for the FPT in SA children it may assist in the accurate diagnosis of CAPD following assessment and contribute to the development of SA specific data. Aim 1: To develop context-specific normative data for the FPT in SA children aged 8- 11 years. Aim 2: To determine the relationship between existing American normative data and newly generated South African normative data. Methodology: A non-experimental comparative descriptive study design was conducted. There were 35 potential participants from 5 schools within the vicinity of the university. Results from 26 participants were included in the study analysis of the FPT and these results were developed into the normative data set. Results: The results from the 26 participants showed that results from the humming response were higher than the verbal response bilaterally. This was noted for all the age groups. In addition, the comparison for the generated normative data and the American data showed no significant difference between the two data sets in the description response. The comparison of the humming response revealed significantly higher responses in the generated normative data over the American data. This was seen across all the age groups. Conclusion: In addressing aim 1, the findings reveal that the FPT as an assessment is not affected by language however, the performance in the test may be affected by the language it is administered in. Additionally, the findings confirm a need for age specific data as the results improved with age showing the neuromaturation of the CANS as the children grow. Regarding aim 2, the results of this study show that there are some differences between the data sets from the two populations which is seen in other studies as well confirming the need for context specific normative data. The data set for this study was small and cannot be generalised to the whole S.A. population, therefore the data may be used as a first step in the development of a full set of normative data for the FPT. The study does inform the need for further research and a larger scale study for context specific data.